The Relationship between Health Outcomes and Household Socio-Economics Characteristics - Dunga, Steven Henry (Journal of Economics and Behavioral Studies, 2019)
The economic circumstance of a household is in most cases linked to the varied situations a household may find itself income is to a greater extent linked to the housing and food that a household is exposed to. Income among other socio-economic factors may also affect the demand structure of the household in terms of what the household may consider necessary or not. The level of household demand for health services and its preventive level may also be associated with other household characteristics especially those associated with the head of the household. This paper analysed the relationship between the morbidity rate in a household and the household characteristics and the characteristics of the head of household. The paper uses data collected in the South African general household survey published in 2017 conducted by Statistics South Africa. Based on a sample of 21601 households, the study employs a multinomial logistic model with the level of morbidity rate categorised into a high level, mild, and low. The results of the empirical analysis show that Household size, the gender of head of household, housing insecurity status age of head of household and income were significant determinants of morbidity rate at the household level. The contribution of the paper is therefore a proposal for preventive mitigation as opposed to treatment which tends to be more expensive on government. The fact that housing insecurity is a competing need with health demand calls for better alignment in terms of government, provision of health services in South Africa. This paper is motivated by the initiative of the introduction of a national health Insurance (NHI) is South Africa.